Annual grants report - Ian Potter Foundation (Melbourne, VIC : The Ian Potter Foundation., 2010)
Grant reports contain grants approved over the past year, reviews of each program area, facts and figures, and reports from the Chairman and CEO.
Also available in print.
Digital file collected and preserved
Description based on: 2016/17; title from pdf file
Keywords: Ian Potter Foundation -- Periodicals; Charitable uses, trusts and foundations -- Australia -- Periodicals; Endowments -- Australia -- Periodicals; Australian